The Impact of Institutional Quality on Income Inequality in Southern African Development Community (SADC) Countries - Dorcas Gonese; Kin Sibanda; Courage Mlambo (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2025)
The study seeks to assess the impact of institutional quality on income inequality in SADC countries from 1980 to 2020 using the pooled mean group (PMG) estimation technique. The study considers six dimensions of institutional quality: government effectiveness, the rule of law, control of corruption, quality, voice accountability, and political rights. The study indicates that different institutional quality measures disparate impact income inequality in SADC countries. Thus, institutional quality indicators such as the rule of law, government effectiveness, regulatory quality, voice accountability, and political stability negatively and significantly affect income inequality. Yet, other institutional quality indicators such as political rights, civil liberties, control of corruption, and corruption perception positively and significantly affect income inequality in SADC countries over the long run. This calls for the SADC governments and policymakers to be cautious about political rights and control corruption when addressing income inequality reduction policies